Design and experimental study on a hybrid adsorption refrigeration system using desiccant coated heat exchangers for efficient energy utilization. (November 2022) - Xu, Jing; Pan, Qaunwen; Zhang, Wei; Liu, Zhiliang; Wang, Ruzhu; Ge, Tianshu
Abstract: Low-grade heat sources at 70 °C exist widely in the nature and industrial fields, which require to be exploited effectively for supplying cooling capacity. Recently, a hybrid adsorption refrigeration system using desiccant coated heat exchangers was proposed to improve the energy efficiency of the adsorption system under low-grade heat sources and achieve multi-mode cooling outputs. In essence, this hybrid system aims to improve the evaporation temperature of the adsorption system by incorporating a terminal which decouples the sensible and latent heat load. In order to validate its feasibility and high efficiency, a 3-kW hybrid system is designed and constructed for the first time, and its performance is tested preliminarily at a 70 °C heat source. The transient characteristics is analyzed and the parametric influence on the system performance is discussed. Experimental results indicate that the hybrid system can be effectively driven by a low-grade heat source at 70 °C with a 30 °C coolant. The effects of the inlet air temperature and relative humidity on the system performance are both positive. A moderate air flow rate (wind speed ∼ 1.2 m/s) is suggested to obtain a promising system performance. The cooling capacity and coefficient of performance can reach 3.95 kW and 0.539, respectively. The performance of the hybrid system is also compared with published studies. Results show that the hybrid system possesses a high efficiency in extracting 70 °C heat sources and satisfies the demand for cooling and dehumidification, which is expected to provide a reference for efficient energy utilization. Highlights: A 3 kW hybrid adsorption refrigeration system is designed, constructed and tested. The hybrid system can be driven by a 70 °C heat source efficiently. The cooling capacity and COP can be up to 3.95 kW and 0.539, respectively.